2013
DOI: 10.1038/ncomms3192
|View full text |Cite
|
Sign up to set email alerts
|

Metformin improves healthspan and lifespan in mice

Abstract: Metformin is a drug commonly prescribed to treat patients with type 2 diabetes. Here we show that long-term treatment with metformin (0.1% w/w in diet) starting at middle age extends healthspan and lifespan in male mice, while a higher dose (1% w/w) was toxic. Treatment with metformin mimics some of the benefits of calorie restriction, such as improved physical performance, increased insulin sensitivity, and reduced LDL and cholesterol levels without a decrease in caloric intake. At a molecular level, metformi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

33
973
5
14

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 1,213 publications
(1,025 citation statements)
references
References 50 publications
33
973
5
14
Order By: Relevance
“…Previously, metformin was found to increase the healthspan and longevity of mice (Martin‐Montalvo et al ., 2013). Given that metformin elevates DICER1 in cultured cancer cells (Blandino et al ., 2012), we wanted to examine whether changes in DICER1 expression occur in mice chronically treated with metformin and to compare these findings with those of mice on dietary caloric restriction, an intervention that extends lifespan in mice.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, metformin was found to increase the healthspan and longevity of mice (Martin‐Montalvo et al ., 2013). Given that metformin elevates DICER1 in cultured cancer cells (Blandino et al ., 2012), we wanted to examine whether changes in DICER1 expression occur in mice chronically treated with metformin and to compare these findings with those of mice on dietary caloric restriction, an intervention that extends lifespan in mice.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we reported that chronic metformin treatment increases both healthspan and lifespan in mice (Martin‐Montalvo et al ., 2013). Here, we have found that DICER1 levels are upregulated by metformin treatment in both mice and humans in part through a post‐transcriptional mechanism involving the RBP AUF1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metformin (Met) has been reported to increase longevity in male mice of the C57BL/6 inbred stock (Martin‐Montalvo et al ., 2013) at a dose of 1000 ppm, started at 54 weeks of age, leading to an increase in mean lifespan of 5.8%. This increase was deemed to be significant using the Gehan–Breslow statistic, which gives greater emphasis to deaths at earlier ages than the log‐rank test used in our own work.…”
Section: Discussionmentioning
confidence: 99%
“…In the ITP dataset, the age at 90th percentile mortality declined by 2% in the Met group. In C57BL/6 mice, Met was toxic at a higher concentration of 10 000 ppm (1%) (Martin‐Montalvo et al ., 2013), and it is possible that evaluation of doses higher or lower than the 1000 ppm dose we used might have produced stronger evidence of benefit. Observational data suggest that patients with diabetes who take metformin have lower mortality risks than age‐matched non‐diabetic patients (Bannister et al ., 2014).…”
Section: Discussionmentioning
confidence: 99%